The correlation of the demographic factors of Filipino-foreign student-athletes on the success of collegiate men's basketball teams in the UAAP from season 84-86 - Santos, Darwin Joseph F. 2000-
Over the years, UAAP has witnessed the inclusion of multiple Filipino-foreign student-athletes which often possesses international exposure bringing dynamic effect to the league due to the high level of competition and diverse playing styles they gained overseas. Filipino-foreign student-athletes or FFSAs are athletes who played the majority of their high school basketball internationally. The objective of this study is to analyze the extent of their impact by analyzing how FFSA demographics—height, number, and player statistics—affect team success during UAAP Seasons 84-86. Secondary data on elimination rankings and win-loss record were first analyzed on all eight UAAP schools where player profiles from each team were then reviewed to identify FFSAs. Elimination round rankings and winning percentages served as metrics of success, with data sourced from official UAAP records and media publications. Statistical analyses, including Spearman Rank Correlation and regression techniques, revealed that the number of FFSAs per team had no significant correlation with success in Seasons 84 and 85. However, in Season 86, height emerged as a significant factor, positively influencing rankings and winning percentages. This study addresses a gap in the literature on the contributions of FFSAs to Philippine collegiate sports, particularly in the UAAP. By exploring the evolving role of FFSAs, this research advances understanding of their optimization for team success and competitive balance in the UAAP.